Successful 7-Year Eculizumab Treatment of Plasmapheresis-Resistant Recurrent Atypical Hemolytic-Uremic Syndrome due to Complement Factor H Hybrid Gene: A Case Report - Vondrák, K; Seeman, T (Transplantation proceedings, 2018)
Atypical hemolytic-uremic syndrome (aHUS) is an extremely rare disease, and up to 70% of the patients have a genetic mutation in the encoding components of complement activation or anti-complement factor H autoantibodies. The risk of recurrence after kidney transplantation is 10% to 80%. Eculizumab, a monoclonal antibody that binds complement protein C5, has shown to be highly effective in patients with aHUS; however, there are only few reports on the efficacy and safety of long-term eculizumab treatment in children with recurrent aHUS. Only 3 case reports regard treatment in patients with complement factor H (CFH/CFHR1/CFHR3) hybrid gene. This report presents the efficacy and safety of long-term eculizumab treatment in a child with recurrent aHUS who has been successfully treated with eculizumab for more than 7 years. The patient presented as a 9-year-old with aHUS due to CFH/CFHR1/CFHR3 hybrid gene and received deceased donor kidney transplantation. After the transplantation, he experienced recurrence of aHUS 2 months later. Daily plasma exchanges were ineffective in the transplanted kidney; the patient became anuric and hemodialysis was needed. Eculizumab was started as therapy and led to complete remission of aHUS including restoration of diuresis. Eculizumab has been given as therapy for 7 years. The young patient is in a sustained remission without any adverse events. This patient is only the sixth patient reported with recurrent aHUS due to CFH/CFHR1/CFHR3 hybrid gene and is the patient with the longest remission of recurrent aHUS ever published.
Keywords: mutace; Recurrence; dítě; Complement Activation; Antibodies, Monoclonal; časové faktory; aktivace komplementu; Time Factors; lidé; atypický hemolyticko-uremický syndrom; recidiva; pooperační komplikace; Mutation; transplantace ledvin; Kidney Transplantation; komplement - faktor H; Male; Postoperative Complications; monoklonální protilátky; humanizované monoklonální protilátky; Child; Antibodies, Monoclonal, Humanized; mužské pohlaví; Atypical Hemolytic Uremic Syndrome; Complement Factor H; Humans